MATLAB based design and performance analysis of electronically commutated BLDC motor - Issa Etier; Anci Manon Mary A.; Nithiyananthan Kannan (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The main objective of this research work is to design the electronically communtated brushless direct current (BLDC) motor and analysis its performance in MATLAB environment. The use of BLDC engine is expanding daily, the performance analysis is progressively significant and the consumer loyalty is significant. In light of the ranking and requirements, the BLDC engine is planned. The BLDC motor is widely used in a variety of fields. Low ripple input supply and a suitable speed controller are needed to achieve desired motor output. The output of BLDC motors, such as torque, voltage, and speed response, is examined in this paper. The controller parameters have been fine-tuned to improve motor speed. It has been discovered that a three phase voltage source inverter (VSI) fed BLDC motor with a fractional-order proportional-integral-derivative (FOPID) controller provides superior BLDC motor response. The outcomes are broke down utilizing the MATLAB programming.